Knowing what not to do: Financial literacy and consumer credit choices - Christian D. Dick; Lena M. Jaroszek (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2013)
Based on a rich panel of household data, we investigate the determinants of the use of consumer credit in Germany. We find that the usage frequency of an easily accessible, but relatively expensive source of consumer credit decreases with financial literacy but is unrelated to household income. This result is robust to household structure, age, formal education, and occupational status. Based on childhood-related information on spending behavior, we control for the influence of self- control on credit decisions. We document that neither self-control, nor low numeracy drive out financial literacy when explaining the frequency of (expensive) credit usage. Hence, financial education plays an important role to improve consumer choices.
urn:nbn:de:bsz:180-madoc-337095
Keywords: D12; D14; 330; Consumer finance; credit decisions; financial literacy; financial education; numeracy; self-control